The Association Between Persistent White-Matter Abnormalities and Repeat Injury After Sport-Related Concussion - Brett, Benjamin L.; Wu, Yu-Chien; Mustafi, Sourajit M.; Saykin, Andrew J.; Koch, Kevin M.; Nencka, Andrew S.; Giza, Christopher C.; Goldman, Joshua; Guskiewicz, Kevin M.; Mihalik, Jason P.; Duma, Stefan M.; Broglio, Steven P.; et al. (Frontiers in Neurology, 2020)
Objective: A recent systematic review determined that the physiological effects of concussion may persist beyond clinical recovery. Preclinical models suggest that ongoing physiological effects are accompanied by increased cerebral vulnerability that is associated with risk for subsequent, more severe injury. This study examined the association between persistent diffusion tensor imaging signal following clinical recovery of sport-related concussion and risk of re-injury. Methods: Average mean diffusivity (MD) was calculated in a region-of-interest (ROI) in which concussed athletes (n=82) showed significantly elevated MD acutely after injury (<48 hours), at an asymptomatic timepoint, 7-days post-return to play (RTP), and 6-months relative to controls (n=69). The relationship between MD in the identified ROI and risk of sustaining a subsequent concussion over a 1-year period was examined with a binary logistic regression. Results: Eleven of 82 concussed athletes (13.4%) sustained a second concussion within 12 months of initial injury. Mean MD at 7-days post RTP was significantly higher in those athletes who went on to sustain repeat concussion within 1 year of initial injury than those who did not (p=.048; d=.75). In this underpowered sample, the relationship between MD at 7-days post-RTP and risk of sustaining a secondary injury approached significance (X2(1)=4.17, p=.057; B=0.03, SE=0.017). Conclusions: These preliminary findings raise the hypothesis that persistent signal abnormalities in diffusion imaging metrics following concussion may increase the risk for repeat concussion. This may reflect a window of cerebral vulnerability or increased susceptibility following concussion, though understanding the clinical significance of these findings requires further study.